Anti-proteasome autoantibodies contribute to anti-nuclear antibody patterns on human larynx carcinoma cells. Issue 1 (30th June 2006) - Feist, E; Brychcy, M; Hausdorf, G; Hoyer, B; Egerer, K; Dörner, T; Kuckelkorn, U; Burmester, G-R
Abstract : Background: Autoantibodies to the 20S proteasome represent an unspecific but common serological phenomenon in patients with systemic autoimmune diseases. Interestingly, a high prevalence of these antibodies have been observed in patients with connective tissue diseases, where anti-nuclear antibodies (ANAs) serve as an important diagnostic screening test. Objective: To disclose interference of anti-proteasome antibodies with known ANA patterns. Methods: Anti-proteasome antibodies were isolated for comprehensive immunofluorescence analyses. The immunofluorescence pattern of human anti-proteasome antibodies was compared with a panel of monoclonal and polyclonal reference antibodies, and colocalisation was analysed using confocal microscopy. Results: Anti-proteasome antibodies clearly contributed to the ANA patterns of their respective serum samples from patients with different rheumatic disorders. In addition to the nuclear pattern, proteasomal staining was also detectable in the cytoplasm, at the endoplasmic reticulum and perinuclear regions showing features overlapping with other known autoantibodies such as those to mitochondria. The specificity of anti-proteasome antibodies was proved by competition experiments and by colocalisation with monoclonal reference antibodies in confocal microscopy. Conclusion: In ANA diagnostics, interference of anti-proteasome antibodies will have to be taken into account, especially in the differentiation of anti-cytoplasmatic autoantibodies.